A Phenomenological Study of Sibaliparri in the Household Life of the Mandar Community in Tapango Barat Village, Polewali Mandar Regency - Nasrul; Najamuddin; A Sakka, Abdul Rahman (Tamaddun Life, 2025)
This study examines Sibaliparriq, a core cultural value of the Mandar people in West Sulawesi, Indonesia, as a lived household praxis that structures cooperation, gender relations, and family wellbeing. While much gender and development scholarship portrays households as sites of persistent inequality shaped by patriarchal norms, less attention has been given to culturally embedded ethics that actively promote reciprocity and shared responsibility between spouses. Adopting a qualitative descriptive phenomenological approach, this study draws on in-depth interviews, participant observation, and documentation conducted in Tapango Barat Village to explore why Sibaliparriq persists in contemporary household life, how it is enacted in everyday practices, and what impacts families associate with its practice. Data were analyzed using Colaizzi’s phenomenological method to capture participants’ lived meanings and moral reasoning. The findings reveal that Sibaliparriq functions as a relational household praxis integrating moral obligation, pragmatic cooperation, and culturally legitimate forms of agency. It is enacted through negotiated household governance, flexible labor sharing across productive and reproductive domains, and collaborative parenting practices. Participants perceive Sibaliparriq as strengthening household harmony, livelihood resilience, women’s recognized participation in decision-making, and the continuity of Mandar cultural identity. Conceptually, the study situates Sibaliparriq within international debates on cooperative–conflict dynamics and women’s empowerment, demonstrating how locally grounded cultural ethics can operate as informal governance mechanisms that reshape gender relations without requiring a rupture from local cultural norms. The study contributes to comparative gender scholarship by highlighting the importance of culturally embedded pathways to cooperation and empowerment in family life.